Proniosomes Used in Cancer Therapy - Devi, M.Kalpana; Parthiban, K.G.; Sangameswaran, B.; Jeevanantham, S. (Journal of Neonatal Surgery, 2025)
Millions of people die from cancer every year, making it one of the world's most serious health issues. Its aggressive behavior and resistance to treatment are influenced by its complex genesis, genetic variability, and capacity to elude immune monitoring. Conventional cancer treatments like chemotherapy, radiation, and surgery frequently fail because of non-specific drug distribution, systemic toxicity, and restricted therapeutic indices, even with improvements in diagnostic and therapeutic techniques. Although they are good at killing quickly dividing cells, chemotherapy drugs can also harm healthy tissues, which can have negative consequences on a patient's quality of life and treatment compliance. Through the creation of specialized drug delivery systems that increase therapeutic efficacy while reducing collateral damage to healthy cells, the area of nanomedicine has recently given rise to fresh optimism. Proniosomes have become one of these new and adaptable drug delivery systems. Proniosomes are free-flowing, dry formulations that transform into niosomes, which are non-ionic surfactant-based vesicles that can hold both lipophilic and hydrophilic medications. Compared to conventional formulations, they have a number of benefits, including as decreased toxicity, regulated drug release, increased chemical stability, and improved bioavailability. Proniosomes use processes like the increased permeability and retention (EPR) effect to enable the targeted administration of chemotherapeutic drugs directly to tumor locations in the context of cancer therapy. This focused strategy reduces exposure to healthy cells, which lessens side effects while simultaneously enhancing medication accumulation in tumor tissues. This paper highlights the revolutionary potential of proniosomes in oncology by examining their structural characteristics, preparation methods, characterisation techniques, and therapeutic uses